The effectiveness of sandplay therapy with a Xhosa child - Snelgar, Orrin Glenn (Rhodes University, Faculty of Humanities, Department of Psychology, 2019)
This case study sought to determine whether Kalffian Sandtray Therapy was effective with a Xhosa child. In the context of ongoing discussions surrounding evidence-based practice and culturally appropriate interventions, no published research has yet explored the effectiveness of this classical tool within this significant South African demographic. In an effort to address this omission, the research adopted a mixed methods approach where Kalffian analysis of the sandplay process was evaluated in conjunction with quantitative measures (the Strengths and Difficulties Questionnaire and the Young Person's Clinical Outcomes in Routine Evaluation). The results of this triangulation revealed a complex picture of improved interpersonal functioning and stagnant (or worsened) emotional wellbeing after five sessions. Contextualised interpretations of these findings are discussed and recommendations made for future sandplay practice and research in the South African context.
Keywords: Sandplay -- Therapeutic use -- Case studies -- South Africa; Play therapy -- Case studies -- South Africa; Child psychotherapy -- Case studies -- South Africa; Children, Black -- Psychology -- South Africa